Berpikir Kritis Siswa dalam Menyelesaikan Soal Literasi Numerasi Berdasarkan Disposisi Matematis - Kurota A’yun; Annafi Awantagusnik (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe students' critical thinking skills in solving numeracy literacy problems by considering their mathematical dispositions. Critical thinking skills are an important competency in 21st-century learning because they play a significant role in understanding concepts, analyzing information, and solving problems with a logical and systematic approach. Numeracy literacy, as part of basic mathematical competencies, requires students not only to be able to calculate but also to understand the context and apply mathematical concepts in real life. In this context, mathematical disposition—which includes self-confidence in mathematics, persistence in solving problems, and curiosity—is seen as a factor that influences students' critical thinking skills. This study used a descriptive qualitative approach with student subjects selected based on high, medium, and low mathematical disposition categories. The instruments used consisted of a numeracy literacy test and a semi-structured interview guide. Data were collected through completing a mathematical disposition questionnaire, working on numeracy literacy problems, and in-depth interviews with selected subjects. Data analysis techniques included data reduction, data presentation, and inductive conclusion drawing. The results of the study indicate that students with a high mathematical disposition tend to have more developed critical thinking skills. They are able to analyze problems in depth, evaluate relevant information, and draw logical and structured conclusions. Conversely, students with medium and low dispositions tend to have limited critical thinking skills, particularly in the aspects of evaluation and conclusion drawing. This finding emphasizes the importance of strengthening mathematical dispositions as an integral part of learning strategies to improve students' critical thinking skills in the context of numeracy literacy.